Many-body interactions in photo-excited lead iodide perovskite1. Issue 17 (7th May 2015) - Trinh, M. Tuan; Wu, Xiaoxi; Niesner, Daniel; Zhu, X.-Y.
<x xml:space="preserve">Abstract</x> Lead halide perovskite is emerging as a promising semiconductor material for thin film solar cells.